PENATALAKSANAAN FISIOTERAPI PADA PASIEN KASUS BELL’S PALSY SINISTRA DENGAN MODALITAS INFRA RED RADIATION DAN MIRROR EXERCISE DI RSUD CIBABAT KOTA CIMAHI - Abdul Qudus; Anjani Nurjanah; Nurul Dwi Ariani (INFOKES (Informasi Kesehatan), 2020)
Bell's Palsy is a neurological disorder and disorder in the cranial nerve VII (facial nerve) in the temporal bone region that causes facial muscle weakness or paralysis around the stylomastoid foramen. To determine the management of physiotherapy in enhancing the functional abilities and strength of facial muscles in the condition of Bell’s Palsy Sinistra by using the Infra Red Radiation and Mirror Exercise modality. After doing therapy for six times the therapy and education can result in an increase in functional activity and muscle strength, namely T1 spasm: (+) there is spasm become T6: (-) no spasm, sensory test T1: 3 (smooth touch, sharp / blunt, temperature sensation) to T6: 1, Ugo Fisch T1: 30 degree "moderate" examination to T6: 70 degrees "good", Manual Muscle Testing (MMT) T1: (frowned = 1, raised eyebrows = 1, closed eyes = 3, nasal deflection = 1, puffed cheeks = 1, smile = 1, blew / kidding = 1) to T6: (frowning = 5, raising eyebrows = 5, closing eyes = 5, flattening nose = 5, puffing cheeks = 5, smiling = 5, blowing / joking = 5).